The effect of institutional ownership on corporate performance: Evidence from China - Yao, DOUDOU (2020)
The objective of this article is to study the impact of institutional ownership on corporate performance, with a greater emphasis on learning whether pressure-sensitive institutional investors (those with an existing or potential commercial transactions with the target company) and pressure-resistant investors (simply maintaining an investment relationship with the target firm) have a different impact on firm value. Besides, state-owned enterprises (SOEs) and non-state-owned enterprises (non-SOEs) are important characteristics of China's capital market. Compared with non-state-owned enterprises, the appointment of the management and the formulation of company business plans in state-owned enterprises are more susceptible to state intervention. Therefore, it is difficult for institutional investors to use their professional advantages and become a qualified supervisor. Based on this reason, it is also significant to test whether institutional investors have a different impact on firm performance between state-owned and non-state-owned enterprises.